2016
DOI: 10.1038/aps.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

The pyrrolidinoindoline alkaloid Psm2 inhibits platelet aggregation and thrombus formation by affecting PI3K/Akt signaling

Abstract: Aim: Psm2, one of the pyrrolidinoindoline alkaloids isolated from whole Selaginella moellendorffii plants, has shown a potent antiplatelet activity. In this study, we further evaluated the antiplatelet effects of Psm2, and elucidated the underlying mechanisms. Methods: Human platelet aggregation in vitro and rat platelet aggregation ex vivo were investigated. Agonist-induced platelet aggregation was measured using a light transmission aggregometer. The antithrombotic effects of Psm2 were evaluated in arteriove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Platelet activation may be induced by a variety of agonists, including AdP and TXA2, which are released from the granules of activated platelets. TXA2 exerts its function through interaction with the thromboxane receptor, contributing to the amplification of the initial platelet activation, which therefore is a principal target for most currently-used antiplatelet agents (31)(32)(33). Although different agonists induce platelet activation through different mechanisms by respectively binding to their specific receptors, they all result in an elevation of intracellular ca 2+ concentration [(ca 2+ )i], an event termed ca 2+ mobilization (34).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation may be induced by a variety of agonists, including AdP and TXA2, which are released from the granules of activated platelets. TXA2 exerts its function through interaction with the thromboxane receptor, contributing to the amplification of the initial platelet activation, which therefore is a principal target for most currently-used antiplatelet agents (31)(32)(33). Although different agonists induce platelet activation through different mechanisms by respectively binding to their specific receptors, they all result in an elevation of intracellular ca 2+ concentration [(ca 2+ )i], an event termed ca 2+ mobilization (34).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, phosphor-Akt can further active endothelial nitric oxide synthase, and ultimately facilitate the migration of ECs, [ 41 ] which is critical to the regulation of vascular homeostasis and angiogenesis. Su et al [ 42 ] pointed out that the inhibition of PI3K signaling could be a promising curative target for thrombotic diseases. An experiment on rat DVT models indicated that overexpressed miR-126 induced an increase in PI3K and phosphor-Akt.…”
Section: Discussionmentioning
confidence: 99%
“…The main targets of the commercially available anti-platelet medicine include ADP receptors, integrin αIIbβ3, and cyclooxygenase but without GPVI and PAR. Upon GPVI activation, the adjacent Src family kinases will initiate the downstream Syk/PLCγ2/PKC signaling [24][25][26]. Miltirone inhibited collagen-and CRP-induced platelet activation in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%